Referenda voting in Portugal, 1998: the effects of party sympathies, social structure and pressure groups - Freire, A.; Baum, M. (European Journal of Political Research, 2003)
According to numerous recent cross-national studies of public support for democracy, citizens of both well-established and newer democracies continue to share a strong commitment to the ideals and principles of representative democracy. Paradoxically, however, these same citizens are increasingly 'critical' of and 'dissatisfied' with the performance of their national democratic institutions. One response has been to call for the 're-invention of government' through the use of referendums and ballot initiatives. This article explores what happens when the national referendum was introduced in Portugal in 1998 - a polity that only recently consolidated its transition to democracy. We examine in some depth the context under which the referendum was introduced and its results in terms of electoral behaviour. The main goals are to explain both abstention and vote choice in the 1998 Portuguese referendums, analysing the role of political parties, social structural factors and pressure groups on those phenomena.